Service Quality and Price Analysis on Customer Satisfaction - Taufik, Edi Rahmat (Management Science Research Journal, 2022)
Hospitals is the institution of public health services in order to improve the level of public health. The success of a hospital in operation is determined by how well the hospital's services are able to satisfy its customers. Basically, customers only want satisfaction from the service they get. Customers will be satisfied if the service they get is able to meet their expectations. In this research, the researchers try to explore about the influence of service quality and price on customer satisfaction on RSIA Puri Garcia, Serang City. The sample was be taken by slovin methode sampling from 692 population are 87 sample of respondent. The result of this research is the service quality and price have an influence on customer satisfaction.